Early-onset ischaemic stroke in a patient with the novel F2 c.1824C>T gene variant and PAI-1 4G/4G, MTHFR 677TT genotype - Pruner Iva; Dinčić Evica; Gvozdenov Maja; Tomić Branko; Kovač Mirjana; Đorđević Valentina (Vojnosanitetski Pregled)
Introduction. Ischemic stroke (IS) is a heterogeneous dis-order caused by several genetic and environmental risk factors. It was suggested that coagulation disorders cause 1-4% of cases with IS, especially in patients with early onset of IS. Case report. We describe a case of a young adult male who developed an unprovoked IS. Biochemical, immunological, and thrombophilia screening, as well as DNA sequencing, were performed in order to reveal molecular pathology underlying the stroke of the patient. Thrombophilia testing showed that patient was a homozygous carrier for PAI-1 4G/5G and MTHFR C677T mutations. Additional genetic analysis revealed the presence of the recently reported F2 c.1824C>T gene variant, located in the last exon of the pro-thrombin gene and has previously been shown to cause hy-perprothrombinemia, hypofibrinolysis, and altered fibrin clot phenotype. Conclusion. Our results suggest that the newly reported F2 c.1824C>T gene variant might have a synergistic effect with PAI 4G/4G and MTHFR 677TT genotype in the formation of altered fibrin clot phenotype characterized by thin, densely packed fibrin fibers, which makes clot less susceptible to fibrinolysis and greatly in-creases the risk for early ischemic stroke onset.